IMPACT OF ECONOMIC GROWTH AND GOVERNMENT SPENDING POLICIES ON CO2 EMISSIONS IN SOUTH SULAWESI: REGRESSION ANALYSIS AND EKC - Sunu Kun Aziz; Ahmad Romadhon; Eko Handoyo (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
In making effective policy responses to climate change, it is necessary to understand the mechanisms that influence CO2 emissions, given that it is becoming a more urgent global issue. This research investigates how economic growth is affected by the amount of government investment in environmental initiatives, and CO2 emissions in South Sulawesi, Indonesia, using a multiple linear regression and the Environmental Kuznets Curve (EKC) approach. By analyzing secondary data from 2018 to 2022, including Gross Regional Domestic Product (GRDP) per capita, government expenditures on climate change adaptation and mitigation, and CO2 emissions, the research assesses how economic and policy actions impact environmental results. The results reveal that while economic growth significantly increases CO2 emissions, government spending on climate-related activities substantially reduces emissions. However, the EKC model does not provide evidence for the theory that there is a curvilinear relationship between economic growth and CO2 emissions in the area. The results emphasize the importance of government interventions aimed at reducing the environmental effects of economic activities and emphasize the necessity of wisely distributing public funds towards achieving sustainable development goals in South Sulawesi.